Simulated Gastrointestinal Fluids Impact the Stability of Polymer-Functionalized Selenium Nanoparticles: Physicochemical Aspects - Selmani A; Matijaković Mlinarić N; Falsone SF; Vidaković I; Leitinger G; Delač I; Radatović B; Nemet I; Rončević S; Bernkop-Schnürch A; Vuletić T; Kornmueller K; et al. (International Journal of Nanomedicine)
Atiđa Selmani,1 Nives Matijaković Mlinarić,2 Salvatore Fabio Falsone,1 Ivan Vidaković,3 Gerd Leitinger,4 Ida Delač,5 Borna Radatović,5 Ivan Nemet,6 Sanda Rončević,6 Andreas Bernkop-Schnürch,7 Tomislav Vuletić,5 Karin Kornmueller,3 Eva Roblegg,1 Ruth Prassl3 1Department of Pharmaceutical Technology and Biopharmacy, Institute of Pharmaceutical Sciences, University of Graz, Graz, 8010, Austria; 2Laboratory for Precipitation Processes, Division of Material Chemistry, Institute Ruđer Bošković, Zagreb, Croatia; 3Division of Medical Physics and Biophysics, Gottfried Schatz Research Center for Cell Signaling, Metabolism and Aging, Medical University of Graz, Graz, 8010, Austria; 4Division of Cell Biology, Histology and Embryology, Gottfried Schatz Research Center for Cell Signaling, Metabolism and Aging, Medical University of Graz, Graz, 8010, Austria; 5Center for Advanced Laser Techniques, Institute of Physics, Zagreb, 10000, Croatia; 6Department of Chemistry, Faculty of Science, University of Zagreb, Zagreb, 10000, Croatia; 7Center for Chemistry and Biomedicine, Department of Pharmaceutical Technology, Institute of Pharmacy, University of Innsbruck, Innsbruck, 6020, AustriaCorrespondence: Ruth Prassl, Medical University of Graz, Neue Stiftingtalstraße 6, MC2.H.3.31, Graz, 8010, Austria, Tel +43 (0) 316 385-71695, Email ruth.prassl@medunigraz.atBackground: Selenium (Se) is a vital micronutrient for maintaining homeostasis in the human body. Selenium nanoparticles (SeNPs) have demonstrated improved bioavailability compared to both inorganic and organic forms of Se. Therefore, supplementing with elemental Se in its nano-form is highly promising for biomedical applications related to Se deficiency.Purpose: The primary objective of this study was to evaluate the impact of the main gastrointestinal proteins on the physicochemical properties and stability of polymer-coated SeNPs.Methods: SeNPs functionalized with thiolated chitosan or hyaluronic acid were characterized based on their composition, morphology, size, and zeta potential. The stability of these particles was evaluated in simulated gastric and intestinal fluids. Additionally, the interaction propensity between major gastric proteins, such as pepsin and pancreatin, and functionalized SeNPs was investigated with FTIR, fluorescence quenching titrations, and in situ adsorption measurements.Results: The composition of the media, including pH and ionic strength, the chemistry of polymers, and the presence of the proteins, influence the size and zeta potential of the SeNPs. The increase in NP size due to the formation of large agglomerates, along with the decrease in zeta potential magnitude, confirmed the formation of a protein corona. Both pepsin and pancreatin showed a strong affinity to the particle surface. Based on the values of the apparent equilibrium dissociation constant this affinity was more pronounced for positively charged thiolated chitosan coated SeNPs compared to those coated with negatively charged hyaluronic acid. The polymer coated SeNPs displayed antioxidative potential, which could be very beneficial for health conditions associated with Se-deficiency.Conclusion: This study highlights the importance of exploring the characteristics of polymer-functionalized SeNPs under gastrointestinal conditions. Such investigations are important for developing nutritional supplements that can gradually release Se from SeNPs, thereby improving selenium absorption, bioavailability, and safety. Keywords: nanoparticles, thiolated chitosan, hyaluronic acid, gastrointestinal proteins, bio-nano interface, protein corona